Crack growth rate prediction based on damage accumulation functions for creep-fatigue interaction (Fracture and Structural Integrity, 2020)
The present study is concerned with formulation of a model for the creep–fatigue crack growth rate prediction on the base of fracture damage zone concepts. It is supposed that crack growth rate can be determined by integration of damage accumulation rate equations into the fracture process zone for low-cycle fatigue and creep loading independently. In the case of low-cycle fatigue loading the damage accumulation function proposed by Ye and Wang was used as well as a classical Kachanov-Rabotnov power law was employment for the creep damage accumulation characterization. Fracture process zone size is calculated on the base of the nonlinear stress intensity factors concept proposed by Shlyannikov. The background for the proposed general model of crack growth rate under creep and fatigue interaction is given in order to comparison with the experimental data. Experimental study of crack growth rate under creep and fatigue interaction is performed for compact tension specimen made from 20CrMoV5. Crack growth rate carried out at the elevated temperature of 550°C according to ASTM E2760 standard. The predictions of the crack growth rate were compared with the experimental data for the 20CrMoV5 steel obtained at an elevated temperature, and the agreement was found to be satisfactory.
Keywords: Creep-fatigue interaction; crack growth rate prediction; nonlinear stress intensity factors